UPDATING SOIL TYPES DIFFERENCES OF ERODED SLOPE LANDS WITH DIGITAL ELEVATION MODEL (DEM) - Valerii KOLIADA; Pavlo NAZAROK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this work is to demonstrate the algorithm of actions for modern erosion-combating optimization of the land use structure by the example of a specific 30.01 ha study area with the help of updating the eroded soil type differences. Description and refinement of soil type difference was carried out by the way of making soil profiles, half-soil profiles and further surface interpretation on a base of laboratory soil samples results. The creation of a generalized digital elevation model (DEM) also has been taken into account to highlight the determination of slope gradient and the shape of the slope using the archive cartographic material of the scale of 1:10 000. Based on the obtained map of the slopes gradient and the generalized digital model of relief, contours of additional soil type differences were revealed, and appropriate recommendations for their use to precise farming, depending on their belonging to a certain eco-technological groups were presented. Such kind of information in the form of data files provides necessary support for programming the input of fertilizers or soil tillage operations on slopes in system of precise farming.